Suitability of Sand as Improvement to Mechanical Properties of Laterite Soil for Road Subbase. - Tumusiime, Darious (Kabale University, 2024)
Sand is a fine-grained, granular material composed of silica and other minerals. It is commonly used in various industries and applications, including construction, manufacturing, and agriculture. In construction, sand is a vital component of concrete, mortar, and asphalt. It is also used as a base material for roads and pavements, providing stability and drainage. One of the most common uses of sand in road construction is as a subbase material. The sub-base layer is placed beneath the pavement surface and serves as a support structure for the road. It helps to distribute loads and prevent settlement, ensuring the long-term durability and performance of the road. This study investigates the potential of sand as a sustainable and cost-effective alternative for stabilizing Nyakambu laterite, a prevalent soil type in Uganda, for use as subbase material in road construction. The research aims to determine the optimal sand content that can enhance the mechanical properties of laterite, specifically the California Bearing Ratio (CBR), to meet the requirements of the Ugandan General Specification for Roads and Bridges. California Bearing Ratio (CBR) is a laboratory test used to determine the strength and resistance of a soil material to deformation under load. It is widely used in road construction to assess the suitability of soils for use as base materials and subbases. The CBR value is calculated by comparing the load-bearing capacity of the soil to that of a standard aggregate. A higher CBR value indicates a stronger and more stable soil. Experimental results demonstrate that adding sand to Nyakambu laterite significantly improves its CBR values. Test results showed that an optimal sand content of 40% by dry weight was found to achieve the desired CBR of 30% for G30 material, surpassing the requirements for subbase material. However, further increases in sand content beyond 40% led to a slight decline in CBR values. From the study, it can be concluded that Nyakambu laterite treated with 40% sand can be effectively used as subbase material in Ugandan roads, offering a viable and sustainable solution to the challenges posed by weak lateritic soils. This research contributes to the development of more durable and cost-effective road infrastructure in the region, aligning with the goals of sustainable development and infrastructure improvement